Aspectos físico-químico, microbiológico e sensoriais do queijo de coalho defumado com borra de café - Ferreira, Ayrton Senna Fernandes (2018)
With the advancement in food production techniques, as well as the most diverse preparations, food technology becomes a differential factor for the production of innovative foods with different standards of acceptance. Culturally Coalho cheese from northeastern Brazil is a product that generates income for small families and large industries, presents remarkable sensorial characteristics, makes it common to the palate of the people, directly influencing the perception and the identity of the product. Factors such as its conservation can be influenced by presenting large amount of water. Some technological processes could favor its conservation, such as smoking. The objective of this work was to submit the elaborated Coalho cheese, to the process of cold smoking, using the smoke of the coffee draff. To investigate the physical, chemical and physico-chemical characteristics, we used Central Compounding Design (CCD) 22 (factorial) and a central point to evaluate the smoking treatments, using with independent variables the time of smoking (X1) and quantity of coffee grounds (X2). All analyzes were performed in triplicates: pH, moisture, Aa, protein, fat, ash, chlorides and color for coordinates (a *, b * and L *), as well as benzo[a]pyrene determination. Samples T1, T4 and T5 were submitted to microbiological and sensorial analyzes. The averages obtained were compared by Tukey's test 5% (p ≤ 0.05). The effects of the independent variables on the dependent variables were evaluated and analysis of variance (ANOVA). The smoking had a significant effect at the level of 10% (p ≤ 0.1) for color analysis, in relation to the coordinates b* and L*. Samples for T1, T4 and T5 treatments present food safety through microbiological analyzes (Salmonella, estafilococos coagulase positive and coliform at 45 °C. No sample showed a quantity of benzo [a] pyrene at the detection limit. Based on the sensory analysis, the T4 sample showed rejection for the terms flavor and residual taste. Preference order analysis did not show significant difference by the Friedman test, among the selected samples.